Guidance for the procurement of COVID‐19 convalescent plasma: differences between high‐ and low‐middle‐income countries. Issue 1 (20th July 2020) - Bloch, Evan M.; Goel, Ruchika; Wendel, Silvano; Burnouf, Thierry; Al‐Riyami, Arwa Z.; Ang, Ai Leen; DeAngelis, Vincenzo; Dumont, Larry J.; Land, Kevin; Lee, Cheuk‐kwong; Oreh, Adaeze; Patidar, Gopal; et al.
Abstract: Background and objectives: COVID‐19 convalescent plasma (CCP) has been used, predominantly in high‐income countries (HICs) to treat COVID‐19; available data suggest the safety and efficacy of use. We sought to develop guidance for procurement and use of CCP, particularly in low‐ and middle‐income countries (LMICs) for which data are lacking. Materials and methods: A multidisciplinary, geographically representative group of individuals with expertise spanning transfusion medicine, infectious diseases and haematology was tasked with the development of a guidance document for CCP, drawing on expert opinion, survey of group members and review of available evidence. Three subgroups (i.e. donor, product and patient) were established based on self‐identified expertise and interest. Here, the donor and product‐related challenges are summarized and contrasted between HICs and LMICs with a view to guide related practices. Results: The challenges to advance CCP therapy are different between HICs and LMICs. Early challenges in HICs related to recruitment and qualification of sufficient donors to meet the growing demand. Antibody testing also posed a specific obstacle given lack of standardization, variable performance of the assays in use and uncertain interpretation of results. In LMICs, an extant transfusion deficit, suboptimal models of donor recruitment (e.g. reliance on replacement and paid donors), limited laboratory capacity for pre‐donation qualification and operational considerations could impede wide adoption. Conclusion: There has been wide‐scale adoption of CCP in many HICs, which could increase if clinical trials show efficacy of use. By contrast, LMICs, having received little attention, require locally applicable strategies for adoption of CCP.